Case report: A sustained survival benefit of third-line immunotherapy for refractory thymic carcinoma - Meng, Mi; Yu, Bo; Luo, Jie; Bai, Yuju; Li, Lin; Chen, Shicheng; He, Sisi; Ma, Hu (Frontiers in Oncology, 2024)
Thymic carcinoma (TC) is an uncommon type of thymic epithelial tumors. Patients with relapsed or refractory TCs have a poor prognosis. Immune checkpoint inhibitor monotherapy can be applied as a second-line treatment for such cases. This study reported a TC patient who did not respond to conventional chemotherapy and radiotherapy but achieved prolonged partial remission lasting 17 months following the third-line treatment with anti-programmed cell death-1 inhibitor sintilimab. This patient did not experience any serious side effects associated with sintilimab treatment. The above results demonstrated that sintilimab could be a feasible therapeutic option for refractory TC patients.